PENERAPAN FLASHCARD DALAM PEMBELAJARAN MATEMATIKA UNTUK MENINGKATKAN KEMAMPUAN LITERASI NUMERASI SISWA KELAS V DI SDN.060788 MEDAN MAIMUN TAHUN AJARAN 2024/2025: Penelitian Tindakan Kelas - Lidia Merda; Sukmawarti; Wariyati; Marisa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research aims to improve pupil' numeracy literacy through the use of flashcard media in mathematics learning, specifically on the topic of area of plane figures. The research employed the Classroom Action Research (CAR) method, conducted in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. The subjects of the study were 14 fifth-grade students at SDN 060788 Medan Maimun during the 2024/2025 academic year. The findings indicated that the use of flashcards effectively increased student engagement in the learning process and helped them grasp the concept of area in a more concrete manner. Student learning mastery improved from 36% in the first cycle to 72% in the second cycle. These results denoted that flashcard media is effective in enhancing elementary students' numeracy literacy skills.